2020
DOI: 10.1183/13993003.01849-2019
|View full text |Cite
|
Sign up to set email alerts
|

Severe desaturations increase psychomotor vigilance task-based median reaction time and number of lapses in obstructive sleep apnoea patients

Abstract: Current diagnostic parameters estimating obstructive sleep apnoea (OSA) severity have a poor connection to the psychomotor vigilance of OSA patients. Thus, we aimed to investigate how the severity of apnoeas, hypopnoeas and intermittent hypoxaemia is associated with impaired vigilance.We retrospectively examined type I polysomnography data and corresponding psychomotor vigilance tasks (PVTs) of 743 consecutive OSA patients (apnoea–hypopnoea index (AHI) ≥5 events·h−1). Conventional diagnostic parameters (e.g. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
7
31
0
Order By: Relevance
“…Analysis comprising only female patients showed smaller differences between best and worst performers in the frequency content of PPG. Based on previous studies, women tend to perform worse than males in PVT [10,18,25], which was observed in this cohort also (Table 1). Women also exhibit a higher resting heart rate and different cardiac regulation sensitivity [26].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Analysis comprising only female patients showed smaller differences between best and worst performers in the frequency content of PPG. Based on previous studies, women tend to perform worse than males in PVT [10,18,25], which was observed in this cohort also (Table 1). Women also exhibit a higher resting heart rate and different cardiac regulation sensitivity [26].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we aim to examine whether larger within-test variation in reaction times is associated with spectral features of PPG. As earlier literature shows that PVT performance is highly sex-dependent [10,18], we perform the analyses separately for men and women. [20].…”
Section: Pvtmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was also seen by Norman et al who reported that no significant differences exist between the normal and mild OSA groups in traditional sleep parameters and differences only emerge when considering the sleep continuity with survival analysis [23]. However, it has to be noted that the division into OSA severity groups is highly artificial and simplistic and the severity assessment with AHI might not sufficiently reflect the physiological effects of OSA [24][25][26]. Therefore, it could be beneficial to study how sleep fragmentation varies when defining the OSA severity differently or even attempt to define the severity of OSA by using sleep fragmentation as a metric.…”
Section: Discussionsupporting
confidence: 57%
“…Hypoxemia, but not AHI, is linked with self-report and objectively measured excessive daytime sleepiness. 40 , 41 Yet, excessive daytime sleepiness, measured by the Epworth Sleepiness Scale (ESS), was not associated with HGS, muscle mass, nor fat mass, in either the unadjusted and adjusted analyses ( Supplementary S2 ). A single previous study showed an ESS score above 15, coupled with self-report snoring or apneic events, is associated with reduced HGS, after adjusting for various confounders.…”
Section: Discussionmentioning
confidence: 99%